O atual e o virtual em Bergson e Deleuze - Henriques, Fernando Meireles Monegalha (2016)
The aim of the present study is to investigate the relations between the concepts of actual and virtual in the philosophies of Henri Bergson (1859-1941) and Gilles Deleuze (1925-1995). We, therefore, make a systematic comparison of the two authors‟ conceptions of temporality based on the three synthesis of time proposed by Deleuze in Difference and Repetition. First, we develop the idea of the living-present in both authors, which is defined as a profound present, i. e. a present equipped with a multitude of degrees or levels of duration through which the immanent relationship between consciousness, body and the material universe takes place. What Bergson and Deleuze call actual is basically the living-present. Afterwards, we study the past in both authors, in order to show that, according to them, our entire past experience is never actually lost, but remains somehow lodged in our immediate consciousness (Bergson) or is stored in a large ontological memory (Deleuze). What Bergson and Deleuze call virtual is constituted by this domain of the past (although Bergson, in contrast to Deleuze, never employs this term as a substantive). After presenting the two authors‟ conceptions of present and past, our aim is to show how they conceived the relationship between actual, virtual and thought. In Matter and memory, Bergson outlines a true theory of knowledge from his theory of actualization of pure remembrance, while in Difference and repetition, Deleuze suggests a complex theory of Idea and thought from his conception about the virtual. However, before studying Deleuze‟s theory of Idea, we concentrate on his third and final synthesis of time – the synthesis of future. Our aim is to show how Deleuze uses it in order to deal with some difficulties resulting from Bergsonism, especially in reference to the possibility of production of the authentic newness, i. e. the creation of something that cannot be reduced neither to the possible nor the past.